The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jort.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Water quality and recreational angling demand in Ireland

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
3
14
0
Order By: Relevance
“…Bass anglers are quite price sensitive; a one-percent change in trip costs diminishes number of bass fishing days by approximately 0.15 percent, ceteris paribus. This is in line with several previous elasticity estimates for angling in Ireland, though these are the first estimates specifically for sea bass angling (Curtis, 2002;Curtis and Stanley, 2016;Curtis and Breen, 2017). The price elasticity for sea angling from Hynes et al (2017) is an exception, where the implied elasticity is -0.6.…”
Section: Econometric Modelssupporting
confidence: 90%
“…Bass anglers are quite price sensitive; a one-percent change in trip costs diminishes number of bass fishing days by approximately 0.15 percent, ceteris paribus. This is in line with several previous elasticity estimates for angling in Ireland, though these are the first estimates specifically for sea bass angling (Curtis, 2002;Curtis and Stanley, 2016;Curtis and Breen, 2017). The price elasticity for sea angling from Hynes et al (2017) is an exception, where the implied elasticity is -0.6.…”
Section: Econometric Modelssupporting
confidence: 90%
“…Note that in our dataset, as reported in Table 3, the mean number of trips is 3.02, while the standard deviation is 3.67, placing the variance at 13.5, over four times the value of the mean. Several others also shown that the NB model performs better than the Poisson model [15,25,26]. Nonetheless, in our estimations the two model estimates are quite similar in magnitude and significance level.…”
Section: Resultssupporting
confidence: 70%
“…Numerous studies have analysed the impact of water quality on recreational water-use demand. Topics have included angling (Bockstael, Hanemann, and Kling 1987;Curtis and Stanley 2016), swimming (Needelman and Kealy 1995), beach visits (Hanley, Bell, and Alvarez-Farizo 2003), boating (Lipton 2004) and many other water-based recreational activities (Binkley and Hanemann 1978;G€ url€ uk and Rehber 2008;Hynes, Hanley, and Scarpa 2008;Paudel, Caffey, and Devkota 2011). A contribution of this paper is its use of revealed user data to determine which water quality measures users are most responsive towards and whether the response varies by recreational activity.…”
Section: Introductionmentioning
confidence: 99%